LA ALIMENTACIÓN COMO REFLEJO DEL DESARROLLO FÍSICO EN DOS COMUNIDADES RURALES DE MÉXICO: CHOLULA E IXTENCO (Revista de História Regional, 2007)
Cholula and Ixtenco are two communities of mesoamericana indigenous tradition in Mexico. Its main economic activity is agriculture which is sustained in corn, beans, chili and squash, so and as one becomes from the pre-Hispanic time. In those communities, multidisciplinary studies have beenmade, between those of agronomy stand out, physical anthropology, archaeology, geography, cultural anthropology and, of course, history. With base in them, we presented an analysis of which the feeding, among other factors, it gave like result in the pre- Hispanic indigenous population and the one of end of century xx. The size of the individuals, after 500 years, it continues beingpractically the same one, and then their nourishingcharacteristics continue being, also, practically the same ones